2017
DOI: 10.1097/iae.0000000000001491
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Subretinal Injection of Tissue Plasminogen Activator and Air in Patients With Submacular Hemorrhage

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Visual outcomes in our patients are like those previously reported in several exudative AMD studies,7 8 11 and had greater improvement than in others 9 10. One study by Gonzalez-Lopez et al reported slightly better outcomes with intervention earlier than 8 days, worse outcomes by area of haemorrhage and a similar overall final BCVA to this cohort at roughly 12-month follow-up 12.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Visual outcomes in our patients are like those previously reported in several exudative AMD studies,7 8 11 and had greater improvement than in others 9 10. One study by Gonzalez-Lopez et al reported slightly better outcomes with intervention earlier than 8 days, worse outcomes by area of haemorrhage and a similar overall final BCVA to this cohort at roughly 12-month follow-up 12.…”
Section: Discussionsupporting
confidence: 87%
“…While prior studies have generally been limited to exudative AMD, this study includes all patients with SRMH regardless of underlying diagnosis. Prior wet AMD series have demonstrated modest visual recovery, anatomic success and relatively few adverse events 7–11. Some natural history studies have suggested worse outcomes of SRMH in patients with CNV, while interventional studies have demonstrated improved outcomes in patients continuing to receive anti-VEGF treatments post-operatively 4 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion what makes our technique more practical and easy to use is that all operative steps can be performed by a single surgeon ( 14 ). No additional time is needed for clot lysis or to prepare special injection devices ( 15 ). There are no studies that compare the functional results of these surgical techniques, so at the moment the choice is strictly related to the comfort and possibilities of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if the blood clot can liquefy earlier, the success rate of operation and surgical effect may be better. Some authors have also used suprachoroidal cavity injection of tissue plasminogen activator 4-5 d after SCH to liquefy the clot[20-22]. Suprachoroidal cavity injection is an intraocular operation which can be performed in some complications, such as retinal detachment, vitreoretinal traction, and vitreous hemorrhage.…”
Section: Discussionmentioning
confidence: 99%